Multiscale analysis of nanoparticles size effects on thermal, elastic, and viscoelastic properties of nano‐reinforced polymers. Issue 8 (11th July 2020) - Blivi, Adoté S.; Bedoui, Fahmi; Weigand, Steven; Kondo, Djimédo
Abstract: Dependency of microstructural organization, thermal, and mechanical properties of reinforced polymers on the size of the fillers was investigated on model nano‐reinforced polymers. Binary systems made of poly(methyl methacrylate) and silica spheres were prepared. While volume fraction was kept constant, silica sphere diameters were varied from 500 nm down to 15 nm. X‐ray scattering techniques along with static and dynamic mechanical analysis were conducted on the different prepared binary systems. From our experimental results, it appears that decreasing particle size lead to reduced interchain distances which could be interpreted as matrix densification. In addition, intrachain distance reflecting distance between two carbonyl groups within the same chain was also affected by particle size. Decrease of such distance was interpreted as local segmental rotation induced by size reduction. From mechanical aspects, reducing the size enhanced elastic properties, as evidenced by the increase in the elastic modulus. Dynamic analysis also confirmed such trend where the storage modulus increases for sample with smaller silica particle. Chain mobility quantified through the composite glass transition and the damping factor revealed size‐induced mobility restriction through the observed increase of the glass transition. Particle size, when less than 60 nm, appeared as an important parameter contribution to material properties enhancement through multiscale microstructural characterization and mechanical analysis. Abstract :